The fauna of crustaceans (Crustacea) of the National Nature Park "Dvorichanskyi", Kharkiv Region - Сідоровський, С. А. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The results of the inventory of the fauna of crustaceans (Crustacea) of the National Nature Park "Dvorichanskyi" for 2010–2013 are presented. Altogether, 16 species of crustaceans were found. One of the species, Gmelina pusilla Sars, 1896 listed in the Red Book of Ukraine, was recorded for the Oskol River for the first time and another species, Lepidurus apus (Linnaeus, 1758) is listed in the Red Book of the Kharkiv Region. Alona guttata G. O. Sars, 1862 was found for the first time in the Kharkiv Region for the last 83 years.